Legal Reasoning on Paternity: Discursive Debate on Children Out of Wedlock in Indonesia - Jarir, Abdullah; Lukito, Ratno; Ichwan, Moch. Nur (Universitas Islam Negeri Jakarta, 2023)
This article explains why Indonesian Ulama and Islamic jurists who oppose the Constitutional Court decision have failed to see the progressive norms in Islam and human rights. They argued that the decision determining that the children born out of wedlock have filiation not only with their mother but also with their father contrasted to and has no legal basis in Islamic jurisprudence. Therefore, this paper will provide the rationale of the arguments of Islamic jurists, including Indonesian ulama, and the proponent of the Indonesian Constitutional Court decision. In conclusion, Indonesian ulama and Islamic jurists have been embracing the conservatism point of view, that is static and textual thinking in interpreting the Ḥadith concerning the issue of a child out of wedlock. As a result, they did not accept another interpretation. Other interpretations are delivered by classical Islamic jurists like Ibn Taimiyyah and Ibrahim al-Nakhā'ī, who argued that a child out of wedlock has a civil relationship with their parents. Meanwhile, the proponent of the Indonesian Court decision adheres to the progressive point of view that considers the children's public interest. Artikel ini menjelaskan mengapa para ulama dan ahli hukum Islam Indonesia yang menentang keputusan Mahkamah Konstitusi (MK) telah gagal melihat norma-norma progresif dalam Islam dan hak asasi manusia. Mereka berargumen bahwa keputusan yang menetapkan bahwa anak yang lahir di luar nikah memiliki hubungan nasab tidak hanya dengan ibunya tetapi juga dengan ayahnya bertentangan dan tidak memiliki dasar hukum dalam yurisprudensi Islam. Oleh karena itu, makalah ini akan memberikan dasar pemikiran dari argumen para ahli hukum Islam, termasuk ulama Indonesia, dan pendukung keputusan Mahkamah Konstitusi Indonesia. Kesimpulannya, para ulama dan ahli hukum Islam Indonesia selama ini menganut pandangan konservatisme, yaitu pemikiran yang statis dan tekstual dalam menafsirkan hadis tentang masalah anak di luar nikah. Akibatnya, mereka tidak menerima penafsiran lain. Padahal, ada penafsiran lain disampaikan oleh para ahli hukum Islam klasik seperti Ibnu Taimiyyah dan Ibrahim al-Nakhā'ī, yang berpendapat bahwa anak di luar nikah memiliki hubungan keperdataan dengan orang tuanya. Sementara itu, pendukung putusan MK menganut pandangan progresif yang mempertimbangkan kepentingan umum-anak-anak.